Intra-Articular injection of acid-sensitive stearoxyl-ketal-dexamethasone microcrystals for long-acting arthritis therapy - Yang Xu; Ziqi Chen; Zunkai Xu; Yanyan Du; Jianghao Han; Xiaoyong Yuan; Shubiao Zhang; Shutao Guo (Elsevier, 2021)
Despite advances in treatment of chronic arthritis, there is still a strong need for the development of long-acting formulations that can enable local and sustained drug release at the inflamed tissues. In this work, we fabricated microcrystals of an acid-sensitive stearoxyl-ketal-dexamethasone prodrug for treatment of arthritis. Microcrystals of the prodrug with two sizes were successfully engineered and showed pH-dependent hydrolysis kinetics in vitro. In a collagen-induced arthritis rat model, we evaluated the influence of particle size and injection dose on anti-inflammatory effect after intra-articular injection. Such prodrug demonstrated long-acting anti-arthritis effects with good safety. Our results indicate ketal-based prodrugs are promising for the development of long-acting injectables and may stimulate the development of new treatments for chronic diseases.